I decided to look at the graphs of the parabola to solve this problem. These are only two types that will fit this problem: parabolas that "open" upwards and parabolas that "open" downwards. These parabolas would never touch the $x$-axis, and this rules out the upwards opening parabola because $a+b+c>0$. However, I am not sure how to continue from here.


Define $f(x) = ax^2 + bx + c$. If $f(0) = c \geqslant 0$, note that $f(1) = a + b + c < 0$, by continuity $f$ has a zero on $[0, 1)$.

  • $\begingroup$ Is there a way to answer my question using the work I have so far? $\endgroup$ – Gerard L. Mar 10 '18 at 2:03
  • $\begingroup$ Now since it must be a downward-open parabola, if $c > 0$, it will cross the $x$-axis at some point by looking at the graph. $\endgroup$ – Saad Mar 10 '18 at 2:05

By the quadratic formula a parabola has roots at $x = \frac {-b \pm \sqrt{b^2 - 4ac}}{2a}$ if such is a real number.

The only way for there not to be roots is if $b^2 - 4ac < 0$. Or if $b^2 < 4ac$.

If $c > 0$ then for this to happen we must have $0 < b^2 <4ac$ so $a > 0$ as well.

But $a+b+c < 0$ so $b$ must be negative. "More negative than $a,c$ are positive". In other words $b < -(a+c)<0$ or $|b| > |a+c|$.

So $b^2 > (a+c)^2 = a^2 + 2ac + c^2$

Now by AM-GM $a^2 + c^2 \ge 2 \sqrt{a^2c^2} = 2ac$

So $b^2 > a^2 + 2ac + c^2 > 4ac$ and thus real roots exist.


To get a grasp geometrically.

$ax^2 + bx + c = a(x^2 + \frac ba x) + c= a(x^2 + \frac ba x + \frac {b^2}{4a^2}) + c - \frac {b^2}{4a^2}) = a(x + \frac b{2a})^2 + c - \frac {b^2}{4a})$.

$a$ tells whether the parabola "goes up" or "goes down". $c - \frac {b^2}{4a})$ is the y value of the tip of the parabola.

to Not have roots either the tip is above the $x$-axis and it points up ($c > \frac {b^2}{4a}; a > 0$. Or the tip is below the $x$-axis and it points down ($c < \frac {b^2}{4a}; a < 0$).

In second case if $a < 0$ then $c< \frac {b^2}{4a} < 0$.

If the first case $c >0$ and $4ac > b^2$. ... which puts us where we were above.


We have $ax^2+bx+c=0$ has no real roots.

Assume that $c=0$, we will have $\Delta=b^2-4ac<0$ or $b^2<0$, which is wrong.

Assume that $c>0$, we will have $\Delta=b^2-4ac<0 \Rightarrow 0\le b^2<4ac$ leads to $c>0$, $a>0$.

If $a+b+c<0$ is correct, then $0<a+c<-b \Rightarrow (-b)^2>(a+c)^2\ge 4ac$ (Cauchy inequality)

$\Rightarrow \Delta=b^2-4ac \ge 0$, contradiction.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.